G443(P) "CHAPS" handover tool in Paediatric setting. (7th April 2014) - Kulkarni, AM; Shetty, S; Damda, F
Abstract : Introduction: Effective handover is vital for patient safety and good patient care. With shift patterns and junior members of staff with variable experience in Paediatrics, a structured handover tool is essential to make handover process effective and efficient. Aim: To assess usefulness of a structured handover tool CHAPS. "C: Clinical picture H: History A: Assessment P: Plan S: Sharing of information" amongst junior members of staff in a busy Paediatric unit in a District general Hospital. Methods: It was a prospective study. The handover tool CHAPS was introduced to junior members of staff. 4 weeks after introduction a structured questionnaire was sent to all junior members of staff contributing to handover to assess their opinion about this tool. The study was done over period of 6 weeks from October 2013 to November 2013. Results: The questionnaire was sent to total 16 junior members of staff which included registrar, Paediatric trainee, GP trainee, Foundation trainee. 12 of 16 members of staff responded to the questionnaire. All 12 who responded agreed or strongly agreed that the tool makes handover efficient. 83% of respondents felt that CHAPS tool makes handover consistent for patients. 75% of respondents agreed that the tool gives optimum information about patients. All disagreed that CHAPS handovers system is poorly structured. Majority of members of staff (83%) felt that CHAPS handover tool has overall improved quality of handover and patient care. 10 out 12 respondents felt that CHAPS tool has helped them by increasing confidence in handing over patient care in a Paediatric unit. Conclusion: "CHAPS" offers an efficient, consistent, sustainable and structured handover tool which works well in Paediatric setting. It helps junior members staff with limited Paediatric experience, structure their handovers resulting in improved quality of handover and patient care.